Religiosity of Cybersex Perpetrators: Case Study of Quran Memorizer Students from Islamic Boarding School Backgrounds - Albadri, Asyya Azzahra; Djamal, Nani Nuranisah; Sulianti, Ambar (Jurnal Psikologi Islam dan Budaya, 2024)
Cybersex behavior as one of the impacts of technology in the field of information and communication has been rife in various circles, including Hafiz Qur'an students with Islamic boarding schools backgrounds at one of the Islamic-based universities in the city of Bandung. It was found that two cybersex offender subjects were Hafiz Qur'an students with Islamic boarding schools backgrounds. Therefore, this study aims to see the religiosity of the two subjects. This study uses a qualitative method with a case study approach. Data collection was carried out by interview and observation methods. The results showed that there were various images of religiosity in each aspect of the two subjects and found religiosity factors, especially in the experience factor of the two subjects as victims of bullying at Islamic boarding schools as well as the factor of individual needs for the presence of storytellers and fulfillment of emotional affection from both parents who making the two subjects start looking for friends virtually but in the end become perpetrators of cybersex.